2016
DOI: 10.1074/mcp.m115.050989
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Proteogenomic Analysis of Plutella xylostella Larval Midgut Using a Multialgorithm Pipeline

Abstract: The diamondback moth, Plutella xylostella (L.), is the major cosmopolitan pest of brassica and other cruciferous crops. Its larval midgut is a dynamic tissue that interfaces with a wide variety of toxicological and physiological processes. The draft sequence of the P. xylostella genome was recently released, but its annotation remains challenging because of the low sequence coverage of this branch of life and the poor description of exon/intron splicing rules for these insects. Peptide sequencing by computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 79 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…Peptide digestion was performed following the previously reported protocol ( Wen et al, 2014 ; Zhu et al, 2016 ). Briefly, 100 μg of each membrane protein sample was subjected to sequential treatment including denaturation with five times the volume of acetone, reduction with 10 mM dithiothreitol, and alkylation with 55 mM iodoacetamide.…”
Section: Methodsmentioning
confidence: 99%
“…Peptide digestion was performed following the previously reported protocol ( Wen et al, 2014 ; Zhu et al, 2016 ). Briefly, 100 μg of each membrane protein sample was subjected to sequential treatment including denaturation with five times the volume of acetone, reduction with 10 mM dithiothreitol, and alkylation with 55 mM iodoacetamide.…”
Section: Methodsmentioning
confidence: 99%
“…Amongst these, 16 proteins (8.3% of total NSAF) are components of the small ribosomal subunit and 27 proteins (10.6% total NSAF) belong to the large ribosomal subunit. This abundance of ribosomal proteins has already been observed [23,34]. Within the most abundant proteins, several are involved in energy metabolism such as the F0F1-type ATP synthase (0.78% and 0.57% respectively).…”
Section: Functional Categorization Of the Detected Proteins And Relatmentioning
confidence: 77%
“…Proteogenomics, the alliance of genomics and proteomics, has proved its efficiency in supporting the existence of genes encoding hypothetical proteins or with unknown function, and even unannotated in the genome for several organisms [20]. This methodology is even more appropriate when a quick focus on mechanisms for which the main players are unknown is required [21][22][23]. Because, proteogenomics is based on the assignment of MS/MS spectra with a six-frame translation of the genome, time-consuming, resource-dependent and hard-working genome sequence completion steps are bypassed.…”
mentioning
confidence: 99%
“…It is still an open question concerning the guidelines for peptide and protein identification data [27]. Recent publication in top journals on proteomics showed that proteins could be unequivocally identified with at least one unique peptide [28,29]. Since the sample in this work is extremely degraded in archaeological context, adopting the above threshold could reveal more solid information.…”
Section: Resultsmentioning
confidence: 99%